Limited Knowledge About Hydatidosis Among Farmers in Northwest Portugal: A Pressing Need for a One Health Approach - Mateus, Teresa Letra (2016)
Hydatidosis is a re-emerging disease. Farmers are a vulnerable population; however, little is known about their awareness of this disease. The purpose of this study was two-fold: (1) to assess sheep and goat farmers' awareness of, perceptions of, and attitudes towards parasitic zoonoses and hydatidosis and (2) to identify the preferred means for promotion of information about hydatidosis. A cross-sectional study was conducted. An in-person questionnaire was constructed and administered to 279 individuals. A coprological survey in shepherd dogs was performed using 88 faecal samples. SPSS version 18.0 was used for statistical analysis. Farmers reported several risk practices (69% practice home slaughtering, 46% do not deworm the dogs, 58% of these dogs have contact with other animals) and very little knowledge about hydatidosis (97% have never heard about it). Nevertheless, 75% of the farmers demonstrated interest in receiving information, mainly from a veterinarian. A wide diversity of potentially zoonotic parasites (Trichuris spp., Ancylostomatidae, Toxocara spp., Taeniidae) was found in 61% of the dogs. This survey revealed farmers' lack of knowledge in relation to hydatidosis and a high prevalence of potentially zoonotic parasites in dogs, thus pointing to the need for health education and a closer collaboration between veterinarian and public health professionals.